2004
DOI: 10.1523/jneurosci.1021-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine–Glutamate Interactions Controlling Prefrontal Cortical Pyramidal Cell Excitability Involve Multiple Signaling Mechanisms

Abstract: Although the importance of dopamine (DA) for prefrontal cortical (PFC) cognitive functions is widely recognized, the nature of DA actions in the PFC remains controversial. A critical component in DA actions is its modulation of glutamate transmission, which can be different when specific receptors are activated. To obtain a clear picture of cellular mechanisms involved in these interactions, we studied the effects of DA-glutamate coactivation on pyramidal cell excitability in brain slices obtained from develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
272
0
10

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(303 citation statements)
references
References 45 publications
21
272
0
10
Order By: Relevance
“…(d) Bar graph summarizing the group data of normalized EPSP amplitude during whole-cell recordings in response to D4 antagonists with little enhancement in Type I pyramidal neurons. component of the evoked EPSP (ie altering the EPSP time course) is consistent with a postsynaptic interaction of D1 and NMDA receptors (Zheng et al, 1999;Seamans et al, 2001a;Chen et al, 2003;Tseng and O'Donnell, 2004). Consistently, anatomical evidence shows that D1 receptor immunoreactivity is frequently associated postsynaptically with dendritic spines and shafts that are in close proximity to asymmetrical synapses characteristic of glutamate receptors (Simley et al, 1994;Goldman-Rakic et al, 2004).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…(d) Bar graph summarizing the group data of normalized EPSP amplitude during whole-cell recordings in response to D4 antagonists with little enhancement in Type I pyramidal neurons. component of the evoked EPSP (ie altering the EPSP time course) is consistent with a postsynaptic interaction of D1 and NMDA receptors (Zheng et al, 1999;Seamans et al, 2001a;Chen et al, 2003;Tseng and O'Donnell, 2004). Consistently, anatomical evidence shows that D1 receptor immunoreactivity is frequently associated postsynaptically with dendritic spines and shafts that are in close proximity to asymmetrical synapses characteristic of glutamate receptors (Simley et al, 1994;Goldman-Rakic et al, 2004).…”
Section: Discussionsupporting
confidence: 69%
“…Whole-cell recording studies have further revealed that DA activates D1 receptors to enhance NMDAmediated responses in both PFC and striatum (Cepeda et al, 1993;Cepeda and Levine, 1998;Zheng et al, 1999;Seamans et al, 2001a;Chen et al, 2003;Tseng and O'Donnell, 2004). On the other hand, the observed inhibitory action of DA (Gulledge and Jaffe, 1998) has been attributed to activation of GABA interneurons via D1 (Gorelova et al, 2002) or D2 receptor activation (Retaux et al, 1991;Grobin and Deutch, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For example, dopaminergic and glutamatergic/NMDA transmission are closely linked in the mammalian brain, particularly in the prefrontal cortex, striatum, and nucleus accumbens (Ferretti et al, 2005;Ikeda et al, 2003;Piomelli and Di Marzo, 1993;Rogue et al, 1990;Takeuchi et al, 2002;Tseng and O'Donnell, 2004;Wang et al, 2003). Medium-sized spiny neurons, the majority of neurons in the neostriatum, receive convergent glutamate-containing afferents from the neocortex and dopamine-containing afferents from the substantia nigra and ventral tegmentum (Murata et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…D1 receptor activation has both excitatory and inhibitory effects on synaptic activity in the PFC, augmenting excitatory NMDAmediated synaptic responses on pyramidal cells, but also enhancing GABAergic transmission (Zheng et al, 1999;Seamans et al, 2001a, b;Tseng and O'Donnell, 2004). In contrast, D2 receptors, which reside on pyramidal cells, local circuit interneurons, and presynaptic terminals (Vincent et al, 1993;Sesack et al, 1995) reduce the excitability of PFC projection neurons while at the same time attenuating GABAergic activity (Seamans et al, 2001a;Tseng and O'Donnell, 2004;Trantham-Davidson et al, 2004). D4 receptors have also been localized in the PFC (Mrzijak et al, 1996;Ariano et al, 1997;Wedzony et al, 2000), and have been shown to reduce both GABAergic and NMDA-mediated transmission (Wang et al, 2002(Wang et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%